Revisionary notes on the genus Adelungia Melichar, 1902 (Hemiptera: Cicadellidae, Megophthalminae), with the description of a new genus - Gnezdilov, Vladimir M.; Neimorovets, Vladimir V. (Zootaxa, 2023)
Leafhopper genus Adelungia Melichar, 1902 is reviewed. Spathicerula Gnezdilov gen. nov. is described with Adelungia calligoni Oshanin, 1908 as the type species, and a new combination—Spathicerula calligoni (Oshanin, 1908), comb. nov., is proposed. Adelungia tridigitata Dlabola, 1984 is placed in synonymy under A. calligoni. Lectotypes are designated for Adelungia elegans Melichar, 1902 and A. breviceps Kusnezov, 1931 to stabilize the nomenclature in the group according to the International Code of Zoological Nomenclature.